Approaches to Lexicography in English and Arabic - M. Ali al-Ubaidy, Sundus; al-Utbi, Mahdi I. Kareem (lark, 2019)
Lexicography, the art and craft of dictionary-making, is as old as writing. Since its very early stages several thousands of years ago, it has helped to serve basically the every-day needs of written communication among individuals in communities speaking different languages or different varieties of the same language. Two general approaches are distinguished in the craft of dictionary-making: the semasiological and the onomasiological. The former is represented by usually-alphabetical dictionaries as such, i.e. their being inventories of the lexicon, while the latter is manifested in thesauruses.English and Arabic have made use of both approaches in the preparation of their dictionaries, each having a distinct aim ahead. Within the confines of each language, an approach may yield various trends as to, for instance, the arrangement of entries within a dictionary.The present paper aims at distinguishing the various trends in writing dictionaries in both English and Arabic. By so doing, it is hoped that the bases on which variation has relied are arrived at in order to provide the appropriate explanations of how and why differences have followed. To achieve this aim, an expository critical account of the approaches to the compilation of monolingual dictionaries in English and Arabic is presented; reference to bi-lingual dictionaries is going to be made appropriately, however. These trends, or schools, within each approach followed a certain system in compiling its representative dictionaries.